(untitled) (Journal of Organizational Psychology, 2020)
The purpose of this research is to examine the impact of employee ownership on organizational commitment and job satisfaction in the context of French listed companies. We analyzed the impact of employee share ownership on organizational commitment and job satisfaction by conducting a survey among employees of French SBF 250 companies. The responses collected were analyzed using the structural equation method. Our results show the existence of a positive and strong relationship between the practice of employee share ownership and organizational commitment and job satisfaction.